INDONESIA'S URGENT NEED TO JOIN THE INTERNATIONAL CRIMINAL COURT (AMID HUMAN RIGHTS VIOLATIONS CONTEXT). - Oktavia Ajeng Kartika Dewi; Felicia Miyuki Luntungan; Petra Novita; Aisyah Zafira Usman; Najwa Khalilatur Rahmah (Problematika Hukum, 2021)
This research was conducted to find out the tendencies of the ICC from the perspective of Rome 1998. Using normative juridical research methods. International Criminal Court (ICC) permanent independent and international tribunal to try the crimes of genocide, crimes against humanity, war crimes, and crimes of aggression, such as the four major international crimes of a host is humanism generis character. Humanitarian crimes, war crimes, genocide, and aggression constitute a serious violation of rights Human rights (HAM). The crime is classified as the most serious offense seriously so always pay attention internationally. There is an international focus on this practice gross violation of human rights does not matter the world is tamed with practice Human rights are harsh. Unfortunately, so far, there have been many perpetrators of gross human rights violations that cannot be tried in the country where crime is earned (Locus Delicti). In general, the perpetrators of gross human rights violations a real person donation regimes tend to do its author protection. Another reason is that the perpetrators have not or have not been tried Serious crime is a legal system that in the country where the crime occurred it's not enough to fight fair trial of the author. Indonesia will get many benefits by becoming a member country and by incorporating into national law the provisions of the Rome Statute by Indonesia.Keywords: Rome statute, human rights, Indonesia, ICC